Al-Khasais al-Islamiyah fi kitab al-lughah al-'Arabiyah li al-Marhalah al-Ibtidaiyah: dirasah manhajiyah li intaj tolib shamil wa muta'adidat al-thaqafat = Islamic characteristics in the elementary Arabic language textbook: produce holistic and multicultural students - Ahmad Bahari, Adilah; Ahmad H.Osman, Rahmah; Mohd Ghadzali, Nur Syaheerah; Mohamad Nor, Ain Farhani (Al Hikmah Research and Publication Centre., 2022)
This study was conducted as a result of the achievement of the goal of Islamic education at the First World Conference on Islamic Education in Makkah Al-Mukarramah in 1977 AD. As one of the most predominant recommendations of that conference is the implementation of a comprehensive and integrated educational system, acknowledging that the current conditions in most countries of the Islamic world's educational and educational institutions do not represent the Islamic image, and do not play their correct role in bringing up generations on the guidance of Islam in worship, perception, and behavior patterns. In addition to emphasizing the significance of the Arabic language in comprehending Islam, this research intends to apply Islamic characteristics derived from the Qur'an and Hadith and related to each topic in the textbook for Malaysian primary school curricula. According to the findings of this study, the value of Islamization can be implemented in the selected topic of the subject: “Sports day” acquired through the Arabic Language textbook for primary 6 and the understanding of Islam and the Arabic language may be linked and applied in the student's daily life from a global and multicultural perspective.